in vitro' studies on the effect of 5-bromodeoxyuridine on cell differentiation - Dyne, Marlen (My University, 2015)
This Project Report identifies, in the Dairy Industry, a market . need which can be satisfied by the development of an annular laminar flow convection assisted milk pasteuriser. It is shown, through experimental work on a full sized model, that the original design concepts envisaged were unsound, but that a revised design could prove to be commercially viable. Mathematical relationships are derived relating to the specific flow and heat exchange conditions. Comparison of these results with existing publications enhances the findings of some other workers, while casting doubt on the validity of certain accepted material. In keeping with modern farming trends, the report examines the feasibility of PC usage in this application and offers it as an alternative to a proprietary control system.